Unveiling living dead: characteristics and consequences of zombie firms - Sadia Rashid; Kanwal Iqbal Khan; Adeel Nasir; Tayyiba Rashid (Cogent Business & Management, 2022)
The increasing number of zombies is becoming a thread for industrial growth due to their inefficiency and lack of performance. Previous studies show that zombies inhibit the growth of non-zombies and prevent the emergence of new ones. However, there is still a lack of research on the consequences of zombies on industrial growth. Therefore, this study aims to investigate the potential characteristics of the likelihood of zombie firms and analyze their impact on industrial growth. Data were extracted from publicly traded companies on the Pakistan Stock Exchange from 2009-2019. Results confirm the presence of zombie firms in the Pakistani context with low liquidity, low solvency, non-profitability, inefficiency, and relatively younger. Moreover, the findings demonstrated a negative link between zombie firms and industrial growth. It states zombie enterprises negatively impact industrial growth as high industrial indebtedness decreases the chances of industrial growth. These findings may be helpful to policymakers when developing insolvency rules to ensure a stable environment for industrial growth.
Keywords: G3; L1; L2; 650; firm-level characteristics; industrial growth; interest coverage ratio; non-viable firms; profitability; zombie firms